2020
DOI: 10.1002/mc.23249
|View full text |Cite|
|
Sign up to set email alerts
|

lncRNA CERS6‐AS1 as ceRNA promote cell proliferation of breast cancer by sponging miR‐125a‐5p to upregulate BAP1 expression

Abstract: Long noncoding RNAs (lncRNAs) can act as oncogene and tumor suppressor genes in many types of cancers including breast cancer (BC). Our previous study has indicated microRNA (miR)‐125a‐5p was downregulated and function as a tumor suppressor in BC. However, its upstream regulation mechanism is still unclear. In this study, we used bioinformatics algorithms, RNA pulldown assay, and dual‐luciferase reports assay to predict and confirm lncRNA CERS6‐AS1 interacted with miR‐125a‐5p. Then we found CERS6‐AS1 was upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Accumulating studies have uncovered that cytoplasmic lncRNAs can directly bind to miRNA and act as a miRNA sponge. [22][23][24] Following bioinformatics prediction, 23 miRNAs were identified to have complementary sites within LINC00239 ( Figure 3C). Of these candidates, miR-629-3p, 25 miR-106a-3p, 26 miR-660-5p, 27 miR-484, 28 miR-320b/c/d, 29,30 and miR-320a-3p 31 were selected for follow-up studies because of their important roles in carcinogenesis and cancer progression.…”
Section: Linc00239 Serves As An Endogenous Molecular Sponge For Mir-4mentioning
confidence: 99%
“…Accumulating studies have uncovered that cytoplasmic lncRNAs can directly bind to miRNA and act as a miRNA sponge. [22][23][24] Following bioinformatics prediction, 23 miRNAs were identified to have complementary sites within LINC00239 ( Figure 3C). Of these candidates, miR-629-3p, 25 miR-106a-3p, 26 miR-660-5p, 27 miR-484, 28 miR-320b/c/d, 29,30 and miR-320a-3p 31 were selected for follow-up studies because of their important roles in carcinogenesis and cancer progression.…”
Section: Linc00239 Serves As An Endogenous Molecular Sponge For Mir-4mentioning
confidence: 99%
“…CERS6‐AS1 has been documented to be a tumor facilitator in several cancers. For example, CERS6‐AS1 enhances cell proliferation and tumor growth and inhibits cell apoptosis in breast cancer 9 . CERS6‐AS1 is highly expressed in hepatocellular carcinoma, and this upregulation suggests a poor prognosis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA adiponectin, C1Q, and collagen domain containing (ADIPOQ) functions as a ceRNA for miR‐219c‐3p to modulate tumor protein p53 (TP53) and promotes colorectal cancer cell growth and migration by targeting the miR‐219c‐3p/TP53 pathway 15 . Moreover, CERS6‐AS1 has been revealed to promote cell proliferation by serving as a ceRNA binding to miR‐125a‐5p to positively regulate BAP1 expression in breast cancer 9 . Hence, it was hypothesized that CERS6‐AS1 might act as a ceRNA to affect the development of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, RT-qPCR was used to detect the expression of CERS6-AS1, being found that the content of CERS6-AS1 in gastric cancer tissues increased and showed high expression, and the same was true in gastric cancer cells. In the study of breast cancer by Yan et al, it was found that CERS6-AS1 may improve the proliferation of breast cancer through miR-125a-5p, and the expression of CERS6-AS1 is up-regulated in breast cancer tissues [ 28 ]. Subsequently, CERS6-AS1 was also confirmed to show high expression levels in different pancreatic cancer cell lines [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the study of Xu et al about the mechanism of CERS6-AS1 on pancreatic cancer concluded that CERS6-AS1 also negatively adjusted miR-217 [ 25 ]. The literature shows that lncRNA CERS6-AS1 is used in the research and analysis of a variety of cancer processes, such as hepatocellular carcinoma [ 35 ], pancreatic cancer [ 25 , 36 ], breast cancer [ 28 ], and most of them are related to the poor prognosis of tumors by targeting miRNAs. In other words, CERS6-AS1 has been verified herein to play a role in the gene regulation of miR-567, and might be used as a potential biomarker for prognosis assessment.…”
Section: Discussionmentioning
confidence: 99%